What Do Knowledge Managers Manage? Practitioners’ Discourse In An Online Forum Compared And Contrasted With The Literature - Crane, Lesley (Journal of Knowledge Management Practice, 2011)
Knowledge Management (KM) is an organisational practice which seeks to leverage knowledge within organisations. It is marked by substantial definitional issues, differences of approach, and controversy, yet it remains a practice of organisations globally. KM attempts to address fundamental questions concerning knowledge, its nature and structure, questions which have interested critical social psychologists for decades. This study adopts a discourse analytic (DA) approach to examine how professional KM practitioners construct KM as a practice in their interactional discourse, comparing and contrasting these to issues and debates in the literature. DA sites discourse as the location of action and achievement, which is occasioned and socially interactional: in this paradigm, knowledge is something that we do. A core finding suggests that KM practitioners axiomatically treat knowledge as object: consequently KM may be managing the wrong “thing”. Few discourse studies have been made in this domain, which is rich in potential and interest.